TEACHING METHODS FOR YOUNG TEACHERS IN UZBEKISTAN: TOWARD A MODERN, INTERACTIVE, AND CULTURALLY GROUNDED PEDAGOGY (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
In the context of Uzbekistan's ongoing educational reforms and its strategic orientation toward democratic development, the preparation and methodological support of young teachers play a vital role. This article explores effective teaching methods suitable for early-career educators, highlighting interactive approaches, game-based learning, and project-based methodologies as essential components for engaging modern students. It also considers the socio-cultural mission of education in Uzbekistan and reflects on how national values and global best practices can be integrated to enhance teaching quality.